Why is it important to teach the complexity of the societies that lived in Mesoamerica and the Central Andes before the arrival of the Spanish? (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2025)
The following article seeks to promote reflection on the ways in which the indigenous societies that inhabited these lands lived in the past before the name America was adopted. The ideas conveyed by highly publicized individuals generate controversy and destabilize certain academic consensuses. Educational institutions at all levels play a very important role in this matter, as they cannot remain outside of these controversies. Starting with a date with strong symbolism, October 12th, a bibliographic analysis on this topic is presented, organized around common questions and problems, to consider possible answers and relationships. In this sense, moving toward building a new citizenship with human traits means advancing the construction of new forms of storytelling, first and foremost by recognizing, if not everyone's voice (that would be impossible), at least more of those that official history hasn't presented to us. Appealing to uncertainty as a way of creating and re-creating means working to deconstruct established knowledge.
Keywords: reflection; complexity; indigenous societies